An enhanced macro mobility management scheme in NEMO environment to achieve seamless handoff - Hassan Abdalla Hashim, Aisha; Hassan, Wan Haslina; Islam, Shayla; Saeed, R.A.; Hasan, M.K.; Daoud, Jamal Ibrahim; Khalifa, Othman Omran (IDOSI Publication, 2012)
In NEMO network, handoff is the process in which the Serving MR (SMR) needs to change its point of attachment to the network when it moves from one network to another new network. Usually during handover, firstly the SMR needs to be disconnected from the old network and then it gets connected to a new network. Thus there is a possibility to lose the connectivity from the Internet as well as its Home Agent (HA) and Correspondent Nodes (CNs). During this time, it becomes difficult to send or receive any data packets which results in packet loss and delay. Accordingly for real time applications that depend on timely packet delivery within certain acceptable thresholds will be sensitive to the length of time a SMR loses connectivity while performing handover. In case of this type of applications seamless handoff is generally expected which includes both features i.e. smooth (no or very little packet loss) as well as fast (low delay) handoff. But in accordance with NEMO Basic Support Protocol (NEMO BSP), only one primary Care of Address (CoA) of SMR can be registered with home agent, which affects the handoff performance resulting packet loss and delay. This paper presents an enhanced macro mobility management scheme for NEMO network which integrates improved FHMIPv6 with mobile networks. The main idea of the proposed macro mobility scheme is to apply the improved fast handoff mechanism for the SMR handoff with its Local Fixed Node (LFN) in NEMO network in order to achieve seamless handoff in terms of packet loss and delay. The performance of the proposed scheme is evaluated using simulation approach. The simulation is done using Network Simulator (NS-2). The simulation result shows that the proposed scheme outperforms the standard NEMO BSP in terms of packet loss (packet loss less than 6%).